The Strengthening Factors and Obstacles of "Disposition to Think" in the Holy Quran and its Educational Implications - Azam Rahimi; Fatemeh Vojdani; Mohammad taghi bigdeli (علوم تربیتی از دیدگاه اسلام, 2024)
Creating "disposition to thinking" is an approach that has recently been taken into consideration for cultivating thinking in the world's educational systems; because simply by teaching the "skill" of thinking to the learners, it is not possible to guarantee becoming a thinker. Since intellectual disposition is a cultural phenomenon and originates from interaction with environmental beliefs, values and norms, it is very important to pay attention to cultural elements in the disposition to think. Therefore, the research aim is to identify the strengthening factors and barriers to the disposition to think based on the Holy Qur'an, and as a result, some suggestions for educational systems. For this purpose, 232 verses whose conceptual scope and themes represented the topic of thinking in the Holy Quran were identified and analyzed. After extracting the basic concepts (28 basic concepts), finally, 4 key axes for the strengthening factors and barriers to the disposition to think from the perspective of the Holy Quran were obtained. The results of the present research, from the perspective of the Holy Quran, indicated that making thinking flow requires factors such as: sources and topics for thinking, appropriate methods, protecting thinking from inhibiting factors (obstacles) and strengthening and guiding thinking through facilitating factors. Based on this, it is necessary for educators to play the role of a model for thinking, providing rich and useful content, providing opportunities and activities for thinking and intellectual challenges, hypothesis testing, expanding the capacity of intuitive and esoteric understanding, moral education and refinement of the self can provide the students with a disposition to think.